Data Processing Problems for Multidisciplinary, Mixed-Longitudinal Studies with Application to the Nijmegen Growth Study - van’t Hof, M. A.; Veling, S. H. J.; Kowalski, C. J. (Methods of Information in Medicine, 1977)
As more complex, computer-oriented studies of growth and development are undertaken, it becomes increasingly important that investigators contemplating the initiation of such studies are aware of some of the data processing problems they are likely to encounter. The present paper discusses some of these problems in the context of multidisciplinary, mixed-longitudinal growth studies and the solutions implemented in the Nijmegen Growth Study are documented.
Keywords: Data Processing; Multidisciplinary Growth Studies; Mixed-Longitudinal Designs